TOWARD AN OBJECTIVE ISLAMIC STUDIES - Hasanah, Karimatul (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2016)
One of the issues that haunts contemporary Muslim scholarship is the objectivity of the study of Islamic Studies which they strive for. Among them are groups called insiders and outsiders. Insiders as Islamic reviewers come from Muslims, while outsiders are reviewers of non-Muslims who are often called orientalists. If insiders are considered to be less objective because of their ideological interests as the adherents of Islam, the outsider's unobjectivity is due to their propaganda-oriented study. The problem eventually leads to the solutioncoming upfrom some prominent scholars’ ideas in Islamic Studies, among them are Kim Knot, Abdur Rouf, and Fazlur Rahman. Kim Knot produced a Spatial theory, Abdur Rauf initiated an Empatic Understanding, while Fazlur Rahman formulated objectivity theories. Those three try to make efforts to bridge between insider and outsider so that each can do an objective study, which is not ideologically-subjective biased. This is called intersubjectivity in religious studies.